Accuracy of Different Apex Locaters. (A Comparative in Vitro Study) - Mohammad Munthir Abdulrazzaq; Emad Farhan Alkhalidi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aims: The objective of this in vitro study was to compare the accuracy of the Root-ZX II, Root ZX Mini,i Pex II, Kerr apex ID , Root PI and YD2 electronic apex locators (EALs) in locating the apical foramen.Materials and Methods: Fifty extracted human teeth with mature apices were used. Access cavities wereprepared. In order to make sure that we have an accurate working length of 21 mm the crown was sectionedwith diamond disc (control). The teeth were then embedded in an alginate model to simulate the periodontiumafter that the Canals were irrigated with 2.5% sodium hypochlorite. The actual length and electronic lengthmeasurements were made on each specimen separately by apex locator devices with an aid of a K-type file.Results: Statistical results showed no significant difference between the 6 devices although concerninglocating the apical foramen, Root-ZXII , Root ZX Mini, were accurate 96% of the time to ±0.5mm, where asI pex II and Kerr apex ID were accurate 94% of the time to 0.5 mm from the apical foramen, 44% ±0.5mmfor the Root PI and 44% ±0.5mm for the yD2. Conclusions: All the apex locators were able to determinedthe position of the apical foramen but consequently the Root-ZX II, Root ZX Mini, i Pex II, Kerr apex IDwere more accurate than Root PI and YD2 apex locators.